Relasi Islam dan Politik Menurut Pemikiran Abdurrahman Wahid dan Muhammad Amien Rais - Hilyatul Azkia; Rifda Nur Miftahuromah; Surya Sukti (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2026)
Islamic political thought in Indonesia has evolved in line with social dynamics and the need for a democratic system that is not solely oriented toward power, but also toward moral and religious values. This study aims to analyze the relationship between Islam and politics in the thinking of Abdurrahman Wahid and Amien Rais, as well as their contributions to building an inclusive and democratic political system. The method used is a qualitative literature study approach through a review of various relevant scientific sources. The results show that both figures reject the formalization of Islam as a state ideology but emphasize the importance of Islamic values ​​as an ethical foundation in political life. Gus Dur views Islam as a social ethic that supports pluralism, democracy, and humanity, while Amien Rais emphasizes the concept of social monotheism as a moral basis for realizing justice and prosperity. Thus, their thinking demonstrates that Islam can coexist harmoniously with modern democracy without having to be realized in the form of a formal Islamic state.